Development of Flood Monitoring System - Chua, Yean Fang (Universiti Teknologi PETRONAS, 2017)
Flood is one of the natural disasters that occurs every year in Malaysia. It destroys the infrastructure and causes fatalities. Flood monitoring system can monitor the flood level and warn people upon the danger of the flood. Existing flood monitoring techniques include hydrological modelling, image classifications and wireless sensor networks are the current measure control. Unlike the existing systems, this project intends to develop a more robust and durable system which can withstand the wet weather condition. It aims to monitor the water level and water velocity then alert the communities in the future implementation whenever there is risk of flood occurrence. In order to do this, the system needs to have the basic information such as water conditions, water level and water velocity.